Penyuluhan Kesehatan Mengenai Penyuluhan Pencegahan Bebas Gagal Ginjal 15 Tahun Mendatang Di Sdn 03 Kabawetan Desa Sumber Sari,Kecamatan Kebawetan,Kabupaten Kepahiang - Gusnawati F, Riska; Sonia I, Putri; Bagaswara, Azi; Hanila, Rese; Febriani, Emi; Rohani, Tuti; Darmawansyah, Darmawansyah; Azissah, Danur (Jurnal Dehasen Untuk Negeri, 2025)
Kidney disease is one of the significant health problems in Indonesia. According to data from the Ministry of Health of the Republic of Indonesia, the prevalence of acute kidney disease (PGA) in Indonesia reaches 15% of the adult population, with numbers increasing every year (Kemenkes RI, 2020). Umber Sari Village Objective : At the end of the counseling process, after participating in counseling activities, it is hoped that children can understand and understand the concept of acute renal failure. Methods : The methods used in counseling about Kidney Disease Free in the Next 15 Years are lectures, educational videos and questions and answers and distributing leaflets. Results and Discussion: showed an increase in the knowledge of students and parents regarding the prevention of kidney failure. Before counseling, only about 30% of participants had good knowledge about kidney function and risk factors that can cause kidney failure. However, after counseling, the percentage increased to 80%. This shows that the counseling method used is effective in improving participants' understanding.